Interweaving Humanism and Islamic Theology: A Comprehensive Inquiry into Amar Ma’ruf Nahi Munkar - Afandi, Akham Jazuli (Proceedings of International Conference on Muslim Society and Thought, 2024)
Religious violence, causing societal friction, especially in diverse Indonesian communities, is often linked to the enforcement of Amar Makruf Nahi Munkar, a principle in Islamic theology. This article aims to trace the root cause of this issue by analyzing the humanist elements in Islamic theology, particularly within Amar Makruf Nahi Munkar. Religious violence, causing societal friction, especially in diverse Indonesian communities, is often linked to the enforcement of Amar Makruf Nahi Munkar, a principle in Islamic theology. Using descriptive and hermeneutic methodologies, the study explores various interpretations of this concept among Islamic scholars, including Qâdi ‘Abd al-Jabbâr, al-Ghazali, and al-Zamakhsarî. The in-depth review reveals that Amar Makruf Nahi Munkar encompasses key humanist values that can be applied in real-life situations, advocating for a gradual approach to promoting goodness based on the individual’s competence and appropriate methods, distancing it from violent and rigid impressions.